Accuracy in Identifying Rice Plant Diseases UsingMethod Fuzzy - Sri Handayani; Gunadi Widi Nurcahyo; Sumijan Sumijan (Institute of Computer Science (IOCS), 2021)
Rice is one of the most favored crops by the Indonesian people, because of its many benefits, especially as a staple food for Indonesians, and is also used as a raw material for the feed and food industry. In particular, rice is processed to produce rice which contains high carbohydrates, so that rice is widely used and used as a human staple food. Some things that often happen at this time by rice farmers, many losses caused by rice plant diseases that are too late to be identified, causing crop failure. In this case, this rice plant disease is still in a mild stage, but many farmers ignore it, so that a bigger and wider problem arises and it is too late to control. The purpose of this study is to assist rice farmers in identifying rice plant diseases, which will use the Tsukamoto fuzzy method and implement it into the system, so that farmers do not feel overwhelmed again in identifying rice plant diseases. In general, Fuzzy can be referred to as uncertain logic but its advantage is that it is capable of the punishment process so that its design does not require complex mathematical equations. There are various fields that can be used by fuzzy logic, one of which is to identify rice plant diseases